1935
DOI: 10.1524/zkri.1935.92.1.190
|View full text |Cite
|
Sign up to set email alerts
|

Struttura Cristallografica del Gruppo Isomorfo (Si4+, Ti4+, Zr4+, Sn4+, Hf4+) P2O7

Abstract: Sn i+ , Hf i+ , costituiscono, a quanto risulta dall'esame microscopico dei loro cristalli e dalle loro formule chimiche, una serie isomorfa cubica, nella quale si devono probabilmente aggiungere quelli di Ge i r c di Th i+ , non ancora preparati, e quello di U i+ che è già stato ottenuto sotto forma di piccoli cubottacdri (1).L'interesse della determinazione strutturale di questo gruppo è grande tanto dal punto di vista cristallografico, quanto da quello chimico, poche non è stata compiuta finora per nessun c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1957
1957
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In ZrP2OT, Zr 4+ is surrounded by 6 equally spaced oxygen ions at the corners of an octahedron, 2.018A distant from the zirconium ion (6). In BaZrO3, the ZrO6 s-octahedra have 6 equally spaced oxygen ions located at 2.09A from the Zr +4 ion (7).…”
Section: Discussionmentioning
confidence: 99%
“…In ZrP2OT, Zr 4+ is surrounded by 6 equally spaced oxygen ions at the corners of an octahedron, 2.018A distant from the zirconium ion (6). In BaZrO3, the ZrO6 s-octahedra have 6 equally spaced oxygen ions located at 2.09A from the Zr +4 ion (7).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it has generally been assumed that octahedral coordination of Si by O occurs only in phases produced at high pressures. However, strong chemical evidence has long existed for the occurrence of octahedral SiO6 in complexes of Si with such ligands as acetylacetone (Dilthey, 1903) or pyrocatechol (Rosenheim, Raibmann & Schendel, 1931), while Levi & Peyronel (1935) showed that it also occurred in one of the polymorphs of SiPzO7. More recently, Bissert & Liebau (1969) and Liebau & Hesse (1969) have shown that it occurs in two further polymorphs of this composition.…”
Section: Experimental Methods Structure Determination and Refinementmentioning
confidence: 99%
“…AM O phases were initially thought to have the simple cubic structure shown in Fig. 1 (8), which can be described in terms of corner sharing AO octahedra and MO tetrahedra, tetrahedra themselves sharing one corner to form M O units. However, several workers realized that the symmetry of these structures would lead to unrealistically short M}O}M bridging bond lengths.…”
Section: Introductionmentioning
confidence: 99%